2017
DOI: 10.1139/cjfas-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the spatial distribution of larval fish abundance provides essential information for management

Abstract: Productive fisheries are strongly linked to the ecological state of the essential habitats. In this study, we developed a methodology to assess the most important reproduction habitats of fish by using larval survey data and Bayesian species distribution models that predict the spatial distribution and abundance of fish larvae. Our case study with four commercially and ecologically important fish species in the coastal zone of the northern Baltic Sea demonstrated that the production of fish stocks can be conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 47 publications
1
59
0
Order By: Relevance
“…Such limits, for example, along temperature and salinity are typical for large variety of taxa in aquatic domains (MacKenzie et al, 2007;Kotta et al, 2019). With SSDMs Vanhatalo et al (2012), Shelton et al (2014), Golding and Purse (2016) and Kallasvuo et al (2017) have demonstrated the benefits of semiparametric models in such situations. The GP approach for modeling environmental responses is similar to generalized additive models (Guisan et al, 2002) but the latter have not been implemented as JSDMs.…”
Section: Response Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such limits, for example, along temperature and salinity are typical for large variety of taxa in aquatic domains (MacKenzie et al, 2007;Kotta et al, 2019). With SSDMs Vanhatalo et al (2012), Shelton et al (2014), Golding and Purse (2016) and Kallasvuo et al (2017) have demonstrated the benefits of semiparametric models in such situations. The GP approach for modeling environmental responses is similar to generalized additive models (Guisan et al, 2002) but the latter have not been implemented as JSDMs.…”
Section: Response Functionsmentioning
confidence: 99%
“…However, predictions using these covariance functions revert to prior predictive distributions when predicting beyond covariate range covered by data. Hence, in extrapolation tasks stationary covariance functions may not be the optimal choice (Vanhatalo et al, 2012;Kallasvuo et al, 2017) and combining the multivariate GP models with functional constraints (e.g. Kotta et al, 2019) could improve their predictive performance further.…”
Section: Response Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species distributions and occupancy models usually use only occupancy data and model patterns instead of demographic processes (Pearce and Ferrier 2001, Sileshi 2007, Keith et al 2008, Duff et al 2012. Although species distribution models built on abundance data give a more detailed view of the relationship between population density and the environment (Kallasvuo et al 2017), they still implicitly assume a simple relationship between patterns of occupancy and abundance (Sileshi et al 2009, Dallas andHastings 2018). Models of abundance conditioned on covariates that use for example a Poisson or negative binomial distribution yield occupancy probabilities as a simple function of the distributional form (Holt et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Rivers are complex aquatic ecosystems that exhibit zonal variation in physical, chemical and biological characteristics, resulting in considerable habitat heterogeneity (Nannini, Goodrich, Dettmers, Soluk, & Wahl, ; Ward & Tockner, ). Fish exploit these diverse fluvial biotopes during different life cycle stages, particularly spawning and early development (Gogola, Daga, Gubiani, Da Silva, & Sanches, ; Kallasvuo, Vanhatalo, & Veneranta, ), without which recruitment is seriously hampered (Humphries & Lake, ). Because population maintenance depends on both reproductive success and recruitment, habitat loss will alter assemblage structure over time, reducing fish stocks and causing local extinction (Agostinho, Gomes, Veríssimo, & Okada, ; Humphries, King, & Koehn, ).…”
Section: Introductionmentioning
confidence: 99%